PENGELOLAAN ORGANISASI, PEMASARAN, KEUANGAN DAN AKUNTANSI KELOMPOK TANI ORGANIK: (Studi Kasus pada Kelompok Tani Organik Manunggal Lestari di Klaten) - Kristanti, Putriana; Andalas, Purwani Retno; Respati, Agustini Dyah (Jurnal Riset Akuntansi dan Keuangan, 2014)
The objective of this community service program is to increase farmers' income Organic Rice Group and Organic Fertilizer Group. The method used in this service is: situation analysis, problem identification, determines the work goals, plans problem solving, social approach, implementation, evaluation and result. Results of this service include: strengthening the organization, improve and develop marketing, accounting, financial management, and drafting of the â€œAnggaran Dasar dan Anggaran Rumah Tanggaâ€ (AD & ART). Keywords: Organic farmer groups, organic rice, organization, marketing, finance